KONSEP ULUMUL QUR’AN SEBAGAI ILMU PENGETAHUAN AL-QUR’AN: 1. Ulumul Qur’an :, 2. Ulumul Qur’an Sebagai Ilmu dan Displin Ilmu - HASNA NURUL AZIZAH; KHUSNUL KHOTIMAH (STIT DARUL ULUM KOTABARU, 2024)
This article exists as a tool or reading to develop Islamic knowledge, especially the sciences contained in the Qur'an. Where the Al-Qur'an is the main source of basic legal sources used by Muslims in the various problems they face. To understand the Qur'an, various knowledge is needed, including